University Students’ Ability In Discourse Type Recognition - Andyani Larasati; Widyastuti Purbani (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
The aim of the study is to identify the discourse type recognition of university students. Descriptive qualitative study was employed to explore the students’ ability in recognizing discourse types. To achieve the objective of the study, a test of discourse type recognition was administered to 25 students of non-English department at a private Islamic university in Yogyakarta. The findings showed that most students found it difficult in recognizing discourse types, the physical form, and the situation in which the discourse types might be found. Other than that, the existence of cultural specificity in discourse types might hinder the students from predicting the proper names for the discourse types. This suggested that the students need to be given more exposures on discourse types and cross cultural understanding to help them identify the discourse types better.